Memory-guided microsaccades - Willeke, Konstantin F.; Tian, Xiaoguang; Buonocore, Antimo; Bellet, Joachim; Ramirez-Cardenas, Araceli; Hafed, Ziad M. (Nature communications, 2019)
Despite strong evidence to the contrary in the literature, microsaccades are overwhelmingly described as involuntary eye movements. Here we show in both human subjects and monkeys that individual microsaccades of any direction can easily be triggered: (1) on demand, based on an arbitrary instruction, (2) without any special training, (3) without visual guidance by a stimulus, and (4) in a spatially and temporally accurate manner. Subjects voluntarily generated instructed “memory-guided” microsaccades readily, and similarly to how they made normal visually-guided ones. In two monkeys, we also observed midbrain superior colliculus neurons that exhibit movement-related activity bursts exclusively for memory-guided microsaccades, but not for similarly-sized visually-guided movements. Our results demonstrate behavioral and neural evidence for voluntary control over individual microsaccades, supporting recently discovered functional contributions of individual microsaccade generation to visual performance alterations and covert visual selection, as well as observations that microsaccades optimize eye position during high acuity visually-guided behavior. Microsaccades are small-amplitude, fixational eye movements that are largely thought to be involuntary. Here, the authors demonstrate that monkeys (and humans) can be easily trained to respond to a remembered target location with a volitional microsaccade, and that a population of superior colliculus neurons is selectively associated with them.